Five-Level Conception Diagnostic Test on Electromagnetic Induction Concepts: Feasibility Test and Overview of Students' Concept Understanding Level - Apriliyanti, Nila; Ermawati, Frida Ulfah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
During the Physics learning process, students often have difficulty in understanding the concepts, such as Electromagnetic Induction concepts. For example, students assumed that a loop in a magnetic field B whose coil plane area shrinks towards the page produces a constant induced electromotive force. However, the truth is when the surface area of the loop is reduced, the induced electromotive force produced gets smaller. This contradiction is called a misconception. This misconception should be detected immediately using a diagnostic test of conception, especially the five-level diagnostic test. This paper is intended to report the results of the writing of a five-level conception diagnostic test for Electromagnetic Induction concepts, to test its’ feasibility (validity and reliability) and to get an overview of the several students’ understanding level as well as to identify the most dominant internal factors that cause students' misconceptions on the concepts. A total of 11 questions on the diagnostic test is validated and reliable therefore it can be used to test students' understanding level. The results of the internal validity test are 92% (very valid) and the external content validity in terms of true fake and wrong fake values are 3.94% and 5.45%, the construct external validity (rxy=0.591) > rtable=0.3061 and the reliability [ r11=0.608 (very reliable)]. Among 14 students who were tested for their level of understanding 44.16% of them experienced a lack of knowledge.